2015
DOI: 10.1371/journal.pone.0128046
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Geometry of Resource Scarcity: Effects of Lean Seasons and Habitat Disturbance on Nutrient Intakes and Balancing in Wild Sifakas

Abstract: Animals experience spatial and temporal variation in food and nutrient supply, which may cause deviations from optimal nutrient intakes in both absolute amounts (meeting nutrient requirements) and proportions (nutrient balancing). Recent research has used the geometric framework for nutrition to obtain an improved understanding of how animals respond to these nutritional constraints, among them free-ranging primates including spider monkeys and gorillas. We used this framework to examine macronutrient intakes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 58 publications
(83 reference statements)
7
83
2
Order By: Relevance
“…Our study indicates that, contrary to the view that howler monkeys are characterized by a low-energy diet and that the protein-to-fiber ratio is a good predictor of their food choice, black howler monkeys adopted a strategy which allowed them to consume, during certain periods of the year, leaves low in available protein or high in fiber. Our results add to the increasing evidence that primates use multiple strategies [Felton et al, 2009;Irwin et al, 2015Rothman et al, 2011Behie & Pavelka, 2012a] to reach their nutritional and energetic requirements and do so by mixing food items that vary in nutrients, minerals, antifeedants, and energy.…”
Section: Notesupporting
confidence: 59%
“…Our study indicates that, contrary to the view that howler monkeys are characterized by a low-energy diet and that the protein-to-fiber ratio is a good predictor of their food choice, black howler monkeys adopted a strategy which allowed them to consume, during certain periods of the year, leaves low in available protein or high in fiber. Our results add to the increasing evidence that primates use multiple strategies [Felton et al, 2009;Irwin et al, 2015Rothman et al, 2011Behie & Pavelka, 2012a] to reach their nutritional and energetic requirements and do so by mixing food items that vary in nutrients, minerals, antifeedants, and energy.…”
Section: Notesupporting
confidence: 59%
“…A detailed study of a single female chacma baboon ( Papio hamadryas ursinus ) showed that this individual maintained a similar dietary macronutrient ratio across 30 consecutive days, despite eating different combinations of foods on different days (Johnson, Raubenheimer, Rothman, Clarke, & Swedell, ). Other studies, including those of mountain gorillas (Raubenheimer, Machovsky‐Capuska, Chapman, & Rothman, ; Rothman, Raubenheimer, & Chapman, ), black howler monkeys ( Alouatta pigra ) (Righini, ) and sifaka lemurs ( Propithecus diadema ) (Irwin, Raharison, Raubenheimer, Chapman, & Rothman, ), also support the contention that wild primates target a particular balance of macronutrients across a single day or across multiple days.…”
Section: Introductionmentioning
confidence: 87%
“…) and sifakas ( Propithecus diadema , Irwin et al. ), and the more omnivorous chacma baboon ( Papio hamadryas ursinus, Johnson et al. ).…”
Section: Macronutrient Balancing In the Wildmentioning
confidence: 99%